Organizational Culture, Work Environment, and Motivation: Its Impact On Performance ASN - Saryadi; Sundari (Junal Ilmu Manajemen, 2023)
The purpose of this study is to understand the influence or impact of organizational culture, work environment, and motivation in improving ASN performance at the Wonogiri District Civil Service Agency. This study uses 40 employees as respondents. Data analysis used multiple multiple linear regression with reliability validity tests, statistical tests, and classical assumptions also coefficiently of determination. The results of this study indicate that organizational culture has a negative but not significant effect on ASN performance. Work environment and motivation positively and significantly affect ASN performance at the Wonogiri Regency Regional Personnel Agency. The results of the simultaneous test (Test F) show the effect of organizational culture and work environment as well as motivation had a positive and significant on ASN performance. The coefficient of determination obtained R squared is 0,664, which means that the variability of organizational culture, work environment, and motivation can affect the increase in ASN performance by 66,4 % of the rest is 33,6% influenced by other variables outside the modeling.